Childbirth Education for Parents Experiencing Pregnancy after Perinatal Loss - Wright, Patricia Moyle (2005)
Expectant parents who have experienced previous perinatal loss have special concerns, which can be partially addressed by modifying prepared childbirth education courses. This article presents a review of current literature, highlighting the unique needs of expectant parents who have experienced previous pregnancy loss. Modifications to traditional childbirth education courses are suggested, which include addressing parents' grief, managing anxiety, and facilitating communication with health-care providers and others.